Role of Confidence and Supply Chain Strategy during Legitimization of Justice in Countries of Transitional Period - Oksana Khotynska-Nor; Lidiia Moskvych; Alexey Yu. Mamychev; Yury V. Vasilyev; Svetlana I. Kuzina (International Journal of Supply Chain Management, 2019)
In recent years representatives of various sciences began to pay attention to the problems of legitimacy of power, making them the subject of scientific and political discussions by considering the supply chain strategy. At the same time, geopolitical changes in the world put on the agenda the search for effective ways of transition to democracy, which was the impetus to the development of the concept of "transit society" and its separate direction - "transit justice". Instability, as a characteristic feature of this stage of social development, bring significant attention to the legitimacy of power and its institutions. Indeed, this question largely determines the perspectives for stabilizing society. It becomes relevant in relation to justice and court system that represents it. The legitimization of court acts as a prerequisite for the legitimization of other authorities and democratic processes in the state. In the most widespread definition of institutional confidence is an integral element of legitimacy and supply chain provides the process for its better transparency. In regard to court it implies faith in the fairness of its actions and decisions as well as public recognition of its authority. In this article we studied key questions about the role of confidence in the legitimization of justice in the countries of transitional period. We argued that the level of confidence in justice in society is directly proportional to the level of its civil consciousness. The informational nature of both predetermines the need of using of information methods for building confidence in court as a necessary condition for legitimizing justice in transitional society.